Perfect phrases for ESL conversation skills hundreds of ready-to-use phrases that help you express your thoughts, ideas, and feelings in English conversations of all types - Engelhardt, Diane (Perfect phrases series., 2022)
This handy reference will help you navigate social and business situations, with hundreds of ready-to-use English phrases and example dialogues for conversing with friends, collaborating with coworkers, and engaging those around you. And the new edition of this bestselling guide includes a new chapter on tele- and video conferencing, as well as audio recordings, available via app, of typical conversations and key phrase clusters throughout the book"--